Commemoration and reconciliation: the Mohawk Institute as a World Heritage Site. Issue 2 (September 2018) - Groat, Cody
Abstract : The UNESCO World Heritage Convention (1972 ) was conceived with the mandate of protecting cultural and natural sites that represent part of the global narrative of humanity. This article contextualises the Canadian Indian residential school system, and specifically the Mohawk Institute of Brantford, Ontario, within this international convention. In demonstrating how the Mohawk Institute could be a contender for World Heritage status, this article incorporates recommendations from the Truth and Reconciliation Commission that illustrate how commemoration can be used as a tool towards reconciliation.